Analysis of optical absorption and quantum efficiency due to light trapping in a n–i–p type amorphous silicon solar cell with textured back reflector. Issue 4 (29th January 2014) - Iftiquar, S. M.; Jang, Juyeon; Park, Hyeongsik; Shin, Chonghoon; Park, Jinjoo; Jung, Junhee; Kim, Sunbo; Yi, Junsin
<x xml:space="preserve">Abstract</x> Textured back reflector (BR) plays an important role to achieve light trapping in amorphous silicon solar cell. We investigated n–i–p type amorphous silicon solar cell, fabricated on textured BR. The solar cells showed improvement in current density and red response of the external quantum efficiency (EQE) spectra. We used simplified ray diagram along with double reflection model to analyze the EQE because the pyramidal surface texture had apparently little or no periodicity in its surface distribution. The Beer–Lambert's exponential absorption relation was used to estimate photo‐current generation. Experimental results and theoretical analysis indicates that the trapping of unabsorbed light within the cell contributes to enhanced red response to the EQE. A further enhancement in current density and EQE was obtained by double texturing the BR. It appears that in addition to enhanced light trapping, a significant reduction in parasitic absorption of light may also contribute to the improvement in cell performance. The double texturing of the BR led to an increase in surface roughness of the cell, that further helps in the light trapping by introducing increased randomness of the light that is transmitted into the cell. <inline-graphic xlink:href="ark:/27927/pgg55088k5m" content-type="pssa201330291-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />